INTERACTION PROBLEMS OF INTERNATIONAL STUDENTS LEARNING TURKISH AS A SECOND LANGUAGE CENTERED ON THE PURCHASE OF GOODS AND SERVICES - DEMİREL, İbrahim Fatih; SERBES, Birce (Uluslararasi Sosyal Bilgilerde Yeni Yaklasimlar Dergisi (IJONASS), 2023)
International students who learn Turkish as a second language interact using Turkish both in their educational lives and in their daily lives. International students, who frequently interact with teachers, other students and, when necessary, administrators in educational environments, have to interact in their daily lives to purchase goods and services. This study identified the interaction problems experienced by 10 international students from seven different nationalities with C1 language proficiency in purchasing goods and services in Turkey/Kastamonu. Then suggestions were given for their solution. Designed as qualitative research, the study is based on a phenomenology design. The study data were collected face-to-face through a semi-structured interview form prepared by the researchers and submitted to expert opinion. Content analysis was used to analyze the data and the problems students experienced in purchasing goods and services under 5 themes. As a result of the interviews and their analysis, language barriers, inadequacy in reception, emotional reactions, adaptation and cultural differences, and differences due to bureaucratic functioning constitute the center of the interaction problems experienced by students. Interviews with the participants revealed that the most common problems were experienced at the Provincial Migration Administration, followed by telephone operator companies, banks, hospitals, hospitals, dormitories, real estate agents and landlords. As coping behaviors with these problems, they resort to mediated help from someone who knows Turkish better than them and to platforms where interaction is less likely.
Keywords: Comparative and Cross-Cultural Education; Karşılaştırmalı ve Kültürlerarası Eğitim; second language teaching; language barrier; interaction; international students; 4. Education